Probiotic nanocomposite materials with excellent resistance, inflammatory targeting, and multiple efficacies for enhanced treatment of colitis in mice - Yuewen Huang; Hongting Cai; Huipeng Liu; Lixiang Wang; Guangfu Feng; Zizi Ding; Yanquan Fei; Aike Li; Jun Fang (Journal of Nanobiotechnology)
Abstract The occurrence of inflammatory bowel disease (IBD) is relevant to impaired intestinal mucosal barrier and disordered gut microbiota, subsequently leading to excessive production of reactive oxygen species (ROS) and elevated levels of inflammatory factors. Traditional therapies focus on inhibiting inflammation, but the vast majority involve non-targeted systemic administration, whose long-term use may result in potential side effects. Oral microbial therapy has exhibited great application prospects currently in IBD treatment; however, its progress has been slowed by issues with deficient bioavailability, poor targeting of colitis, and low therapeutic efficacy. Consequently, it is exceedingly desirable to develop a strategy by which probiotics can be endowed with additional anti-inflammatory and antioxidant properties, as well as enhanced targeting of the inflamed intestine. Herein, we present an innovative therapeutic strategy for encapsulating probiotic Bacillus coagulans spores with rosmarinic acid (RA) and silk fibroin (SF). Probiotics in spore morphology possessed strong gastrointestinal environmental resistance; RA alleviated oxidative damage by scavenging ROS and inhibited inflammatory responses; SF assisted probiotics release and colonize in the inflamed intestine. We demonstrated the therapeutic efficacy of probiotic composite materials in a colitis mouse model, which significantly alleviated a series of colitis symptoms, inhibited inflammatory cytokine storms, restored the balance of the gut microbiota, and downregulated inflammation-related signaling pathways. We are optimistic that the utilization of therapeutic nanocoating to modify probiotics will open up novel avenues for future microbial therapy targeting IBD.